Return-To-Play Decision Making in Team Sports Athletes. A Quasi-Naturalistic Scenario Study - Mayer, Jochen; Burgess, Stephanie; Thiel, Ansgar (Frontiers in Psychology, 2020)
Competitive athletes act within cultures of risk in sports and often decide to return to sport despite having acute health problems. The outcomes of such risky return-to-play decisions can not only negatively affect their future health, but also limit their sports performance or even upset their career paths. Following risk-management-decision theory with its focus on active risk defusing, we developed a model for understanding the process of return-to-play decision making from an athlete’s perspective. Based on the method of active information search, a quasi-naturalistic return-to-play decision scenario was created in order to assess amateur team sport athletes’ decision making strategies. The main goals were to identify different information acquisition patterns and to analyze the influence of social pressure to play hurt on decision making. A total of 72 competitive team sport athletes (36 females, 36 males, m= 25.7 years of age, 3rd to 6th league level) out of three disciplines (volleyball, basketball, and handball) participated in the experimental study. Facing the same medical scenario (a partial tear of the supraspinatus tendon), athletes show different approaches to return-to-play decision making. The main focus is on potential sporting consequences of withdrawal from competition due to injury, while only few players favoring well-informed decisions based on thorough risk analysis. The athletes who chose the medically risky alternative to play hurt mostly employed strategies of active risk defusing, which got activated when severe sporting consequences were perceived. Those who chose to withdraw from competition primarily referred to maximin heuristic, particularly when social pressure to play was reduced. The findings can be used to improve rehabilitation